The Effect of Risk Perception and Income on Investment Decisions - Tanti Widia Nurdiani; Riduwansah; Rudi Ginting; Gatot Dwiyono; Nini (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines how risk perception and income shape investment decisions among students of the Faculty of Economics and Business at ABC University, Jakarta. The issue is relevant because student investors often enter financial markets with uneven financial literacy, modest income, and different tolerance toward uncertainty. A quantitative design was applied using primary data collected through questionnaires. Since the population was manageable, census sampling was used, and 75 students became respondents. The data were tested with Partial Least Squares (PLS) to assess the direct and joint effects of the independent variables. The findings indicate that risk perception and income influence investment decisions both individually and jointly. The model explains 91% of the variation in investment decisions, while 9% is affected by variables outside this research. Although the explanatory value is high, the result should be read carefully because investment behavior among students may also be shaped by financial literacy, peer influence, digital investment platforms, and market information. This study suggests that better risk understanding and income management can support more rational student investment behavior.